Favorable Molecular Orientation Enhancement in Semiconducting Polymer Assisted by Conjugated Organic Small Molecules. (18th October 2016) - Kang, Minji; Yeo, Jun‐Seok; Park, Won‐Tae; Kim, Nam‐Koo; Lim, Dae‐Hee; Hwang, Hansu; Baeg, Kang‐Jun; Noh, Yong‐Young; Kim, Dong‐Yu
Abstract : A bimodal texturing effect of semiconducting polymers is investigated by incorporating conjugated small molecules to significantly improve the charge transport characteristics via formation of 3D transport pathways. Solution blending of the electron‐transporting polymer, poly{[ N, N ′‐bis(2‐octyldodecyl)‐naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl]‐alt‐5, 5′‐(2, 2′‐bithiophene)} (P(NDI2OD‐T2)), with small molecular crystals of tetrathiafulvalene and tetracyanoquinodimethane is used, and the thin film microstructures are studied using a combination of atomic force microscopy, transmission electron microscopy, 2D grazing incidence X‐ray diffraction, and surface‐sensitive near‐edge X‐ray absorption fine structure. Blended thin films show edge‐on and face‐on bimodal texture with long‐range order and microstructure packing orientation preferable for electron transport through the channel in organic field‐effect transistors, which is confirmed by high electron mobility 1.91 cm 2 V −1 s −1, small contact resistance, and low energetic disorder according to temperature dependence of the field‐effect mobility. Structural changes suggest a 3D network charge transport model via lamella packing and bimodal orientation of the semiconducting polymers. Abstract : Polymer morphology and molecular orientation are significantly changed by introducing conjugated planar small molecules into semiconducting polymer films. Face‐on and edge‐on bimodal texture with better long‐range arrangement and ordered lamellar stacking enhances efficient charge transport in the polymer semiconductor of organic field‐effect transistors.